Transfer of Land Rights through Exchange Originating from Village Treasury Land - Ipok Diva; Aprila Niravita (Faculty of Law, Universitas Negeri Semarang, 2024)
Based on Minister of Home Affairs Regulation Number 1 of 2016, it is possible to transfer rights to village treasury land through the transfer of assets by means of exchange. This research aims to find out how the procedure for transferring land rights by means of the transfer of assets through exchange is reviewed based on Minister of Home Affairs Regulation Number 1 of 2016 concerning Village Asset Management, as well as what the legal consequences are on the status of land resulting from the transfer of land rights through the transfer of assets by means of exchange. This research uses Normative Juridical research, using qualitative data analysis methods presented descriptively. The research results show that Based on Minister of Home Affairs Regulation Number 1 of 2016, the transfer of village assets in the form of land through exchange consists of those for the public interest, not for the public interest and village treasury land other than for the public interest and not for the public interest, where the exchange is for the public interest and not for the public interest. generally have general similarities in procedures The transition requires permission from the Village Government, Regent and Governor with a stipulation through a decree. Meanwhile, the legal consequences for the status of land resulting from the transfer of land rights through the transfer of assets by means of exchange are that the village treasury land that is released will be removed from the village asset inventory list and the applicant can register the land as their ownership with freehold status. Meanwhile, the replacement land will be recorded in the village asset inventory list and will become village treasury land with right-to-use status owned by the village government.